Implementation of the Eco-Metaverse in Indonesia: Sharia Economic Perspective - Insawan, Husain; Alwahidin, Alwahidin; Kira, Horiacheva; Putri, Azzahrah Insawan (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This article discusses the implementation of the eco-metaverse in Indonesia, with a focus on the economic aspects of the metaverse. This article begins by providing an overview of the metaverse concept and its potential impact on various sectors, including education, commerce, and entertainment. Then, this article examines the principles of metaverse economics, such as the concepts of values, principles and norms, and how these concepts can be applied in the context of the metaverse. This research uses a qualitative research paradigm with a sharia economic approach. Data and information were collected through interviews, literature studies and focus group discussions (FGD). The condition of the eco-metaverse in Indonesia has begun to develop, although it is not yet running optimally. Several ways of using the Metaverse that can be considered in the context of sharia economics are Education and Knowledge, Communication and Empowerment, Economics and Business, and Socio-Cultural Life. Eco-metaverse development can be carried out through the waqf and syirkah application model on the sharia banking platform in the metaverse. Apart from that, another model being developed is a platform for selling MSME products through metverse where sellers and buyers can interact directly virtually. Based on the results and discussion in this research, it is highly recommended to; Explaining sharia-based eco-metaverse applications. There is a need for sharia-based eco-metaverse education, so that more and more people build or join the eco-metaverse. In implementing a sharia-based eco-metaverse, institutions are needed that oversee the consistent application of sharia principles in a transparent and interconnected eco-metaverse.